1952
DOI: 10.6028/jres.048.045
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mica

Abstract: A synthetic fluorophlogopite mica (KMg3A1Si30 IO F 2), in which the (OR) ions that are normally found in normal micas were complet.ely replaced by fluorine, has been syn thesized. This material has essentially the same physical and electrical properties as natural phlogopite mica, except with somewhat lower flexibility. To grow large, usable sheets of mica. it is necessary to obtain pr"ferred crystal orientation, which depends primarily on controlled thermal gradients, batch composition, and rate of cooling. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1956
1956
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Referring to mineral alteration of micas, Bloss et al concluded that F − cannot escape from a lattice as an ion, whereas OH − may escape as H 2 O simply by combining with an H + from another OH − ion . Corresponding to that, synthetic pure fluorine‐end phlogopite is characterised by a much higher thermal stability as compared with hydroxide‐end phlogopite . Nevertheless, it could be concluded that fluorine loss occurs because of a release of HF provided that both, F − and OH − , are present.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Referring to mineral alteration of micas, Bloss et al concluded that F − cannot escape from a lattice as an ion, whereas OH − may escape as H 2 O simply by combining with an H + from another OH − ion . Corresponding to that, synthetic pure fluorine‐end phlogopite is characterised by a much higher thermal stability as compared with hydroxide‐end phlogopite . Nevertheless, it could be concluded that fluorine loss occurs because of a release of HF provided that both, F − and OH − , are present.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, fluorine should be released more readily from minerals in which it occurs as an isomorphous replacement in the OH – position as compared with minerals belonging to the first group after Koritnig or pure fluorine‐end member minerals. However, this could be hindered if the mineral structure is additionally stabilised by hydrogen bonds of the hydroxide ions that have been shown to enhance thermal stabilities …”
Section: Discussionmentioning
confidence: 99%
“…A significant practical benefit has come in the synthesis of fluorophlogopite, a mineral closely resembling natural mica, with improvement in high temperature properties resulting from reduction of anionic charge and elimination thereby of virtual water (62). This is the most promising synthetic mica now being investigated in large-scale production, which may reduce our dependence upon a somewhat uncertain natural resource.…”
Section: Synthetic Fluoro-mineralsmentioning
confidence: 96%
“…In trioctahedral micas, the OH dipole is perpendicular to the (001) plane, directed towards the interlayer cation (Bassett, 1960). The OH --~ F substitution at the Mg sites removes the OH.--K repulsion, strengthens the K-O bonds, and explains the unusual mechanical strength of fluorine-rich biotites (Van Valkenburg and Pike, 1952;Takeda and Donnay, 1966;Takeda et al, 1971). A similar but more complex phenomenon occurs in oxybiotite, where strengthening of the K-O bonds comes from the OH ~ O substitution (Barshad and Kishk, 1968;Farmer and Wilson, 1970) related to the Fe 2+ --* Fe 3 § oxidation and the (Fe z+, Mg 2+) 2H_2Ti2 exchange (Filippov et aL, 1976).…”
Section: Polytype Formation and Mechanical Strength: Crystallographicmentioning
confidence: 99%